Understanding Emotional Adaptivity in Study Tools: A Mixed-Methods Evaluation of Eunoia - Das, Tanisi (International Journal of Research in Interdisciplinary Studies, 2025)
Productively tools are increasingly common amongst students. However, these applications do not take into account the impact of emotion on the cognitive characteristics of attention and motivation. Eunoia was developed for this purpose - it is a study assistant that consists of an emotion-adaptive interface which changes the feedback accordingly. This study investigated 17 participants in a within-subjects design, using objective and subjective measures. The findings of this study demonstrated that emotion-adaptive features as a result of self-reported moods were more likely to improve attention and motivation compared to auto-detect emotion and standard study time conditions. Furthermore, Participants seemed to prefer the self-report mode as it provided them with autonomy and control, along with accuracy. Although the auto-detect method was considered helpful, it did not feel trustworthy to a majority of participants. These results indicate that user agency and transparency in affective systems are crucial along with demonstrating the potential of these interfaces in everyday studying contexts.